The Influence of Entrepreneurial Education on Entrepreneurial Attitude through Entrepreneurial Self-Efficacy among Pharmacists - Sunanto, Sunanto; Hady, Hamdy; Veriady Purba, Jan Horas (Riviera Publishing, 2023)
This research aims to find out more deeply about the influence of entrepreneurial education (EE) on entrepreneurial attitude (EA) through entrepreneurial self-efficacy (ESE) in pharmacists in Jabodetabek. The population in this study are all registered pharmacists in the Indonesian Pharmacists Association (IAI) in the Jabodetabek area, and based on the latest IAI data, as of 2022, there are 16,941 pharmacists. Using the Slovin formula, by taking an error of 5%, a sample size of 391 respondents was obtained using proportional random sampling via a questionnaire. Quantitative data analysis using measurement model analysis, structural models, and verification analysis (hypothesis testing) using a structural equation modeling (SEM) approach with the help of Lisrel. The research results showed that the two independent variables, either Entrepreneurial Education (EE) or Entrepreneurial Self-efficacy (ESE), had a positive and significant effect on the Entrepreneurial Attitude (EA) of Pharmacists in Jabodetabek. The higher the EE or ESE, the higher the Entrepreneurial Attitude (EA). EE was also proven to be a significant predictor of ESE. Then, Entrepreneurial Self-efficacy (ESE) significantly mediates the positive influence of Entrepreneurial Education (EE) on Entrepreneurial Attitude (EA) among Pharmacists in Jabodetabek. The results of this research can provide business input for pharmacists as well as input for policy recommendations for related parties in the pharmaceutical entrepreneurship ecosystem.